Evaluasi TPS 3R di Kota Bandung: studi kasus TPS Saling Asih II dan TPS Hikmah - Fitriana Khodijah; Kancitra Pharmawati (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2023)
Area scale TPS 3R is one of the steps taken to reduce the generation of waste entering the landfill. Aspects that support the operation of TPS 3R are legal, technical, institutional, financial, and community participation arrangements. This study aims to determine the steps to optimize TPS 3R as a contribution to reducing waste in the landfill. The research was conducted at two TPS 3R in Bandung City, namely the TPS 3R Saling Asih II and TPS 3R Hikmah. A quantitative descriptive analysis method was applied based on the TPS 3R Technical Guidelines FY 2021 so that a description of TPS 3R and a comparison of the two TPS 3Rs were obtained. The functioning status of TPS 3R Saling Asih II is very good with a total value of 19.15 and TPS 3R Hikmah has a good status with a total value of 17.75. The biggest aspects supporting the functioning of TPS 3R are technical aspects and institutional aspects. Optimization of TPS 3R can be done by socializing waste management to the community in collaboration with stakeholders, and increasing the competence of TPS 3R officers in order to improve the performance of TPS 3R.